Nuclei segmentation for computer-aided diagnosis of breast cancer - Kowal, Marek; Filipczuk, Paweł (Zielona Góra: Uniwersytet Zielonogórski)
Breast cancer is the most common cancer among women. The effectiveness of treatment depends on early detection of the disease. Computer-aided diagnosis plays an increasingly important role in this field. Particularly, digital pathology has recently become of interest to a growing number of scientists. This work reports on advances in computer-aided breast cancer diagnosis based on the analysis of cytological images of fine needle biopsies. The task at hand is to classify those as either benign or malignant.
Keywords: computer-aided diagnosis; breast cancer; pattern analysis; fast marching